EMOTIONAL ABUSE IN ROALD DAHL’S MATILDA - Lenak, Helen V.; Mogea, Tini; Kamagi, Sarah (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This research aims to reveal emotional abuse and its impact on Roald Dahl’s Matilda. This study used qualitative research because the writer collected the data in the form of words, definitions, quotations, statements, or dialogue, which can provide support for this research. In other words, the writer analyzed the data according to the topic and then narratively presented the result. The data sources are divided into two categories: the primary data source is the novel, and the secondary data are journals, articles, e-books, and other sources that are related to the study. In analyzing the data, the writer used a psychological approach to present the emotional abuse and its impact. The results show that the emotional abuse that Matilda experienced was caused by her parents, who criticized her, did not support her, and even manipulated her. So Matilda chooses to read books because reading provides Matilda with a sense of empowerment and freedom. She recognizes that education and learning provide her with a path to empowerment. She finds solace and adventure in books to escape from her difficult situation